Feeding Patterns and Stunting Incidence among Toddler in Coastal Community in Gresik - Najah, Siti Safinatun; Noveyani, Adistha Eka; Simanjuntak, Tri Damayanti; Wati, Dwi Martiana; Ridzkyanto, Ricko Pratama (Journal of Public Health for Tropical and Coastal Region, 2024)
AbstractIntroduction: Despite the plentiful availability of protein from fish and other essential food sources in coastal communities, coastal communities still face the issue of undernutrition. This study aimed to assess the association between feeding practices among toddlers and the incidence of stunting in the coastal area.Methods: We conducted a community-based case-control study in Gresik. We assessed the feeding patterns (feeding practice, food quality, and food safety) of 90 children aged 24–59 months using a structured questionnaire. We generated frequencies and percentages and ran a bivariate test to determine factors associated with stunting using the Chi-Square testResults: The mother’s age among the case and control group was in the ideal age category (<20 and >35 years old). Most respondents among the case group and control group had low family income (less than the wage minimum of Gresik regency IDR 4.372.030,5). Most of the respondents in the case group (57.8%) had low education (junior high school or less). The feeding pattern variable consists of three aspects. In the aspect of food quality, most of the stunting group (62.2%) indicated that children had poor food quality. In the aspect of feeding practices, most of the stunting group (53.3%) indicated that the feeding practices provided were inadequate. In terms of food safety, most of the stunting group (68.9%) had good food safety.There is an association between aspects of food quality with the incidence of stunting (p-value =0.003; OR =3,647; 95% CI 1.524-8.728). There was no association between aspects of feeding practices (p-value=0.138) and aspects of food safety (p-value=0.141) with the incidence of stunting.Conclusion: The feeding patterns of children, especially the food quality aspect, in the coastal area of Gresik Regency significantly influence their nutritional status, with a direct correlation between food quality and the incidence of stunting. There should be an increase in malnutrition interventions in this community, focusing mostly on educating individuals about improving child nutrition by utilizing the food sources that are already available.